EFEKTIVITAS KOMUNIKASI MASYARAKAT DI PERKEBUNAN (STUDY KASUS MASYARAKAT PERKEBUNAN DI SUMATERA UTARA) - Riadi, Selamat (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
Community communication effectiveness in plantations we can put it together in the form of internal and external problems. Effectiveness is the goal of the ability to utilize something right, clear and universally acceptable standard. Community and plantation company conflicts are natural resource conflicts based on the struggle for natural resources. This problem can have an impact on socio-cultural aspects so that it refers to communication problems. The ability to approach problems must be able to master the negotiation, both the ability to dialogue, humility, trust, hope and critical thinking, so that problems in the garden do not expand and will not benefit all parties.